Enhancing Students Metacognitive Awareness and Scientific Reasoning through the Quantum Learning Model in High School - Aeni, Saofiatul; Jufri, A. Wahab; Handayani, Baiq Sri; Ramdani, Agus (Jurnal Pijar Mipa, 2025)
Students’ limited ability to connect theoretical concepts with real-life phenomena, coupled with monotonous lecture-based teaching, has led to low engagement in learning. This study investigates the effect of the Quantum Learning model on students’ metacognitive skills and scientific reasoning. Using a quasi-experimental design with a nonequivalent control group, the study involved 41 tenth-grade students at SMA 1 Labuapi, divided into an experimental group (n = 20) and a control group (n = 21), selected through saturated sampling. The Metacognitive Skills Scale (MSS), adapted from Mustafa and Nuray, and a scientific reasoning test based on the Classroom Test of Scientific Reasoning (CTSR) developed by Lawson, were used for data collection. Data were analyzed using paired sample t-tests at a significance level of α = 0.05. Results showed significant improvement in both groups, with the experimental group experiencing greater gains in metacognitive skills (mean diff. = -20.050; SD = 5.624; p = 0.000) and scientific reasoning (mean diff. = -32.200; SD = 5.978; p = 0.000) compared to the control group (metacognitive: -11.905; SD = 5.558; scientific reasoning: -14.619; SD = 5.826; both p = 0.000). These findings indicate that the Quantum Learning model is effective in enhancing metacognitive awareness as well as scientific reasoning and is recommended for use in science education to improve student engagement and thinking skills.